2011
DOI: 10.1111/j.1530-0277.2011.01567.x
|View full text |Cite
|
Sign up to set email alerts
|

Persistent but Less Severe Ataxia in Long‐Term Versus Short‐Term Abstinent Alcoholic Men and Women: A Cross‐Sectional Analysis

Abstract: Background Disturbed gait and balance are among the most consistent and salient sequelae of chronic alcoholism. Results of small sample longitudinal investigations have provided evidence that partial recovery of gait and balance functions in alcoholics may be achieved with abstinence. However, abstinence durations reported have been limited, and their power and generalizability have suffered from small sample sizes. Methods In the present study we employed a cross-sectional approach to assess gait and balanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
33
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 49 publications
3
33
1
Order By: Relevance
“…Whereas performance was inversely correlated with smoking duration in both smoking groups, it was not related to alcohol consumption across both ALC groups. This is contrary to findings in treatment naive heavy drinkers (Smith and Fein, 2011). While the proportion of nsALC able to perform the WFEC task did not increase between TP1 and TP3 (similar to the nsCON proportion), the proportion of sALC able to perform the task more than doubled by TP3.…”
Section: Discussioncontrasting
confidence: 99%
“…Whereas performance was inversely correlated with smoking duration in both smoking groups, it was not related to alcohol consumption across both ALC groups. This is contrary to findings in treatment naive heavy drinkers (Smith and Fein, 2011). While the proportion of nsALC able to perform the WFEC task did not increase between TP1 and TP3 (similar to the nsCON proportion), the proportion of sALC able to perform the task more than doubled by TP3.…”
Section: Discussioncontrasting
confidence: 99%
“…Prior studies examining the effects of acute alcohol on balance reported that nondependent adolescents who showed little sway in response to acute alcohol were more likely to develop alcohol dependence than youth who exhibited excessive sway (Schuckit, 1994), yet without alcohol challenge adolescents who carry familial risk of alcohol use disorder show greater postural sway than non-carriers (Hill, Steinhauer, Locke-Wellman, & Ulrich, 2009). Further, chronic alcohol dependence in adults can result in significant postural instability that remains detectable even in abstinent alcoholics, although sustained sobriety can result in at least partial resolution of imbalance (Smith & Fein, 2012; Sullivan, Rosenbloom, Lim, & Pfefferbaum, 2000). The predictive value of stability testing performance absent acute alcohol challenge awaits longitudinal study.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the fusiform gyrus and parietal lobe differences in activation between groups in the present study, alcohol users also showed increased activation in structures typically affected by chronic alcohol use, particularly the cerebellum (Smith & Fein, 2011), thalamus (Harding, Halliday, Caine, & Kril, 2000), and prefrontal cortex (Abernathy, Chandler, & Woodward, 2010). Paul et al (2008) examined total cerebral brain volumes in a healthy community sample in low, moderate, and high drinkers in addition to abstainers and previous drinkers.…”
Section: Discussionmentioning
confidence: 87%